Analisis Pengelolaan Water Sport Event sebagai Destinasi Wisata Olahraga di Danau Ranau Kab. Oku Selatan Prov. Sumatera Selatan - Muhammad Iqbal Djohan; Rhiza Eka Purwanto; Yayan Dian Fitriansyah (Politeknik Pariwisata Makassar, 2020)
ABSTRACT Analysis of the Management of Water Sports Events as a Sports Tourism Destination in Ranau Lake, South Oku Regency, South Sumatra Province. The focus of research is to discuss the formulation of the problem and the purpose of this study are: a) To study and analyze how to plan the implementation process and evaluation of the implementation of water sports events in Lake Ranau District. South OKU, South Sumatra Province. b) To study and analyze how the implementation of water sports events in the District. South OKU, South Sumatra Province. c) provide an alternative strategic policy that can be done to optimize the planning process to the implementation of water sports events in the Regency. South OKU, South Sumatra Province. With data collection techniques used are observation, interviews, and questionnaires. The data analysis model used is the SWOT analysis method (Strength, Weakness, Opportunity, Threats). This study population transferred 30 people consisting of the community and the organization in the Lake Ranau area. This research is expected to offer alternative strategies for optimizing, planning and implementing water sports events. KEY WORDS: Management, Water Sport Event (WSE), Destination Lake Ranau